Meningkatkan Kemampuan Mengenal Lambang Bilangan Melalui Kartu Angka Bergambar Bagi Anak Tunagrahita Ringan - Yusniar, Yusniar; Mahdi, Arisul (Jurnal Penelitian Pendidikan Khusus, 2022)
This study aims to prove whether picture number card media canimprove children's ability to recognize number symbols in mildmentally retarded children. This study uses classroom action researchwith the implementation of two cycles. Picture number card mediaaccompanied by colors is a medium that can assist teachers inconveying learning by reducing limitations in delivering material,besides that picture media can provide complete details of what will beconveyed so that children can easily remember it. Based on the resultsof the study, children's ability to recognize number symbols increasedcompared to before using the picture number card media.